Quantification of microbial communities in subsurface marine sediments of the Black Sea and off Namibia - Schippers, Axel; Kock, Dagmar; Höft, Carmen; Köweker, Gerrit; Siegert, Michael (Frontiers in Microbiology, 2012)
Organic-rich subsurface marine sediments were taken by gravity coring up to a depth of 10 meters below seafloor at six stations from the anoxic Black Sea and the Benguela upwelling system off Namibia during the research cruises R/V Meteor 72/5 and 76/1, respectively. The quantitative microbial community composition at various sediment depths was analyzed using total cell counting, CARD-FISH and quantitative real-time PCR (Q-PCR). Total cell counts decreased with depths from 109 – 1010 cells /mL at the sediment surface to 107 – 109 cells /mL below one meter depth. Based on CARD-FISH and Q-PCR analysis overall similar proportions of Bacteria and Archaea were determined. The down core quantitative distribution of prokaryotic and eukaryotic small subunit ribosomal RNA genes as well as functional genes involved in different biogeochemical processes was successfully revealed by Q-PCR. Crenarchaeota and the bacterial candidate division JS-1 and the classes Anaerolineae and Caldilineae of the phylum Chloroflexi were as highly abundant as Archaea and Bacteria, respectively. Less abundant but detectable in most of the samples in high gene copy numbers were Eukarya and the Fe(III)- and Mn(IV)-reducing bacterial group Geobacteriaceae (off Namibia) as well as the functional genes cbbL encoding for the large subunit of Rubisco, the functional genes dsrA and aprA of sulfate-reducers and the gene mcrA of methanogens. Overall the high organic carbon content of the sediments goes along with high cell counts and high gene copy numbers, as well as an equal abundance of Bacteria and Archaea.